2017
DOI: 10.1161/circgenetics.116.001643
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Venous Thromboembolism in UK Biobank Identifies the ZFPM2 Locus and Implicates Obesity as a Causal Risk Factor

Abstract: Background UK Biobank is the world’s largest repository for phenotypic and genotypic information for individuals of European ancestry. Here, we leverage UK Biobank to understand the inherited basis for venous thromboembolism (VTE), a leading cause of cardiovascular mortality. Methods and Results We identified 3290 VTE cases and 116,868 controls through billing-code based phenotyping. We performed a genome-wide association study (GWAS) for VTE with ~9,000,000 imputed SNPs. We performed a phenome-wide associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 48 publications
1
86
0
Order By: Relevance
“…Despite these successes, much of the heritability of VTE remains unexplained. A recent study based on 3,290 VTE cases and 116,868 controls from the UK Biobank estimated the heritability due to genotyped and imputed single-nucleotide polymorphisms (SNPs) to be~30% (Klarin, Emdin, Natarajan, Conrad, & Kathiresan, 2017), and twin studies have estimated VTE heritability to be as high as~50% (Heit et al, 2004). However, the UK Biobank study also noted that known variants only explain 5% of VTE heritability.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these successes, much of the heritability of VTE remains unexplained. A recent study based on 3,290 VTE cases and 116,868 controls from the UK Biobank estimated the heritability due to genotyped and imputed single-nucleotide polymorphisms (SNPs) to be~30% (Klarin, Emdin, Natarajan, Conrad, & Kathiresan, 2017), and twin studies have estimated VTE heritability to be as high as~50% (Heit et al, 2004). However, the UK Biobank study also noted that known variants only explain 5% of VTE heritability.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate and genome-wide association studies (GWAS) have identified seven VTE-associated susceptibility genes ( ABO, F2, F5, F11, FGG, PROCR , and NME7 ) (Germain et al, 2011; Greliche et al, 2013; Heit et al, 2012; Tang et al, 2013; Tregouet et al, 2009). A large meta-analysis of GWAS identified two additional susceptibility genes on chromosomes 10 and 19 ( TSPAN15 and SLC44A2 ) (Germain et al, 2015), and recently, two GWAS newly identified F8 and ZFPM2 genes on X chromosome and chromosome 8, respectively (Hinds et al, 2016; Klarin et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Klarin et al (2017 ) recently reported an association between the T allele of rs6993770 and decreased risk of venous thromboembolism (VTE). They postulated that the underlying mechanism is a ZFPM2 mediated decrease in the plasma concentration of the principal inhibitor of plasminogen activator PAI-1, which is encoded by SERPINE1 (Klarin et al 2019) .…”
Section: Evidence That Zfpm2 Is a Regulator Of Platelet α-Granularitymentioning
confidence: 99%